2017
DOI: 10.1002/bem.22103
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high‐frequency electromagnetic radiation enhances neutrophil response to particulate agonists

Abstract: The growing use of extremely high-frequency electromagnetic radiation (EHF EMR) in information and communication technology and in biomedical applications has raised concerns regarding the potential biological impact of millimeter waves (MMWs). Here, we elucidated the effects of MMW radiation on neutrophil activation induced by opsonized zymosan or E. coli in whole blood ex vivo. After agonist addition to blood, two samples were prepared. A control sample was incubated at ambient conditions without any treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
(79 reference statements)
0
5
0
1
Order By: Relevance
“…Very few studies have examined the effect of this wavelength on this type of cells, but some positive data have been obtained in cells exposed to similar frequencies. Recently, Vlasova et al indicated that 32.9–39.6-GHz exposure enhanced the neutrophil response to particulate agonists [26]. The frequency used in that experiment was similar to the one we used, although power density was almost 10-fold higher, and this difference alone might have affected the results.…”
Section: Discussionmentioning
confidence: 72%
“…Very few studies have examined the effect of this wavelength on this type of cells, but some positive data have been obtained in cells exposed to similar frequencies. Recently, Vlasova et al indicated that 32.9–39.6-GHz exposure enhanced the neutrophil response to particulate agonists [26]. The frequency used in that experiment was similar to the one we used, although power density was almost 10-fold higher, and this difference alone might have affected the results.…”
Section: Discussionmentioning
confidence: 72%
“…Eight in vitro studies were performed [18,20,47,91,97,99,101,102] of which seven reported responses. In one study [99], human blood cells ( ex vivo ) were exposed to MMW for 5, 15 and 30 min (32.9–39.6 GHz, 10 mW/cm 2 ). The activation of the cells was examined in the presence or absence of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that there are practically no data in the literature on changes in the enzymatic activity of lactic acid bacteria exposed to EMF. The authors of [3] presented the results of an experimental determination of lactase activity under different conditions. However, we did not find any results concerning changes in the activity of enzymes of conjugated metabolic pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, as one of the promising methods of influencing biological objects, the action of an extremely high frequency electromagnetic field (EMF EHF) of the millimeter range is considered. Analysis of the data available in the literature allows us to make a conclusion about the possibility of the existence of EHF waves interaction mechanisms with cells of plant or animal origin, which affect the fundamental mechanisms of the functioning of living systems, which leads to significant changes in their physiological activity [1][2][3][4]. Determination of the optimal conditions for the impact of EHF EMF on microbial cells, under which there is a significant shift in the external manifestations of the reaction of microorganisms, allows to intensify biotechnological production.…”
Section: Introductionmentioning
confidence: 99%